Crime and Violence as a barrier to Gender Equality in Nigeria politics. (2011)
Electioneering in Nigeria has been characterised by violence, electoral irregularities and various criminal activities. However the continuous campaign for women to be actively involved in the democratic process has yielded little compare to the increasing number of women heading key positions in other domain. This paper therefore seeks to examine fear of crime and electoral violence in Nigeria as major factors mainstreaming women out of politics. Specifically the study investigates factors endangering women from politics, the trend and pattern of women’s participation in election over the last decade among forty-five (45) key women leaders in the informal economy. The study is anchored on Kanter’s Glass Ceiling theory which explains women's roles in leadership. Collection and interpretation of data for this study were basically qualitative, involving the use of interviews and content analysis. The study recommends a constitutional approach that will stipulate a reasonable, minimum and special security placement for women in every government with little or no cost.